ETOS KERJA GURU DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Erniwati La Abute (Damhil Education Journal, 2021)
The purpose of this study was to determine the work ethic of teachers in improving students’ learning achievement at MTs. Negeri 1 Luwuk. To collect the data, the researcher used direct observation, interview, and docummentation to the teachers, included the Head of Madrasah. The data obtained were analyzed descriptevely. This study resulted two (2) findings, namely (1) the work ethic of the teachers in improving students’ learning achievement has been implemented in obeying all the rules and regulations at MTs. Negeri 1 Luwuk, as well as showing the simplicity, honesty, acted based on common sense, willingness to change or improve the self quality of students’ MTs Negeri 1 Luwuk. (2) the work ethic of the teachers, can be improved through respect for the teachers’ personal self, because respect, recognition of achievements and works, from an economic perspective, politics greatly affects a person's work ethic of the teachers in carrying out their duties. Based on the findings above, it is concluded that; (1) the work ethic of teachers at MTs. Negeri 1 Luwuk, has been proven by the simplicity, high discipline, honesty, mutual respect and appreciate, and have foresight (2) Factors influencing the work ethic of teachers are attention and respect, while affecting the students’ achievement are health, disability, maturity, intelligence, interest, atteantion, as well as family, society/environment and teachers’ factors.